Strategi Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Agroindustri Jenang Kedunggudel di Desa Kenep Kabupaten Sukoharjo - Nabila Threa Fernanda; Kusnandar Kusnandar; Raden Kunto Adi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Agriculture plays a strategic role in Indonesia's economy. However, agricultural products often face challenges such as low prices and susceptibility to spoilage. Further processing is essential to add value to agricultural products, creating opportunities for developing household industries and MSMEs in agro-industry. The processing industry sector is critical in driving economic growth in Sukoharjo Regency. The Penang industry dominates Kenep Village on a micro-enterprise scale. As a traditional food, the Jenang industry faces challenges and opportunities. This study aims to identify the internal and external factors affecting the development of the Jenang Kedunggudel MSMEs in Kenep Village, formulate alternative strategies, and determine the priority strategies for developing these MSMEs. The research method used is descriptive-analytical with both qualitative and quantitative approaches. The research location was purposively selected in Kenep Village, Sukoharjo Regency, with informants chosen based on specific criteria. Data sources include primary and secondary data collected through observation, interviews, and record-keeping. Data analysis involves using IFE, EFE, IE, SWOT, and ANP. Based on the strategic analysis, quality control is the top priority to enhance product quality and prevent damage. Quality control is prioritized because it directly impacts the Jenang Kedunggudel product compared to other strategic alternatives.